EFFECT OF CYMBOPOGON CITRATUS TERPENOIDS AGAINST BACTERIAL PATHOGENS CAUSING BOVINE MASTITIS - *GOPINATH. S.M.; SUNEETHA T.B; SUMER SINGH. (International Journal of Pharma and Bio Sciences, 2013)
Phytochemical analysis of Cymbopogon citratus revealed presence of bioactive compounds such as alkaloids, flavonoids, saponins, tannins, phenols, terpenoids etc. Each of the bioactive compounds were estimated and isolated separately by solvent-solvent extraction for methanolic and aqueous extracts of Cymbopogon citratus. Saponins content was higher in methanolic extracts of Cymbopogon citratus (23.64%). This was followed by terpenoids with highest of all in methanolic extracts (10.2%). Alkaloids were the least present. Isolated bioactive compounds from crude extracts were tested for antibacterial activity against pathogens causing Bovine mastitis such as Escherichia coli, Streptococcus uberi, Staphylococcus aureus, and Coagulase-negative staphylococcus aureus. Terpenoids from aqueous extracts of Cymbopogon citratus have shown antibacterial activity with highest zone of inhibition against E. coli (17mm) and least against E. coli and S. uberis (12mm) by methanolic extracts. Hence terpenoids is important bioactive compounds. Aqueous extracts revealed significant activity as compared to methanolic extracts.